Assessing Trends in Multidimensional Poverty During the MDGs. (9th March 2022) - Burchi, Francesco; Malerba, Daniele; Montenegro, Claudio E.; Rippin, Nicole
Abstract : While we have extensive information on the trends in income poverty, little is known about the trends in multidimensional poverty. The paper tries to fill this gap by assessing the changes in multidimensional poverty in 54 countries since 2000. The analysis relies on two individual‐based indices, the G‐CSPI and the G‐M0, which combine three dimensions: education, health, and employment, derived through the constitutional approach. The G‐CSPI is a distribution‐sensitive index, while the G‐M0 allows decomposition by dimension. The results reveal that more than 80 percent of the countries have reduced multidimensional poverty. However, progress was very limited in sub‐Saharan Africa. Different decomposition analyses indicate that poverty alleviation was mainly driven by a reduction in the incidence of poverty and a decline in health deprivations. A comparison with changes in income poverty suggests that the correlation is not strong and that multidimensional poverty has decreased significantly less.